Is Social Spending Procyclical? - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2010)
This paper studies the cyclical behavior of public spending on health and education in 150 countries during 1987 - 2007. It finds that spending on education and health is procyclical in developing countries and acyclical in developed countries. In addition, education and health expenditures follow an asymmetric pattern in developing countries; they are procyclical during periods of positive output gap and acyclical during periods of negative output gap. Furthermore, the degree of cyclicality is higher the lower the level of economic development.